O Grupo Escolar Minas Gerais e a educação pública primária em Uberaba (MG) entre 1927 e 1962 - Souza, Marilsa Aparecida Alberto Assis (2012)
This study is aimed at investigating the process of creation and installation of Grupo Escolar Minas Gerais, as well as identifying the pedagogical practices experienced in the institution in its early years of operation. This is the second educational institutional in the city of Uberaba/MG, created in 1927, but installed approximately seventeen years later. The study is organized in two parts. In the first, it was investigated the reasons why the institution that had already been built since 1930 only started working in 1944. It was also investigated how the city provided education to the school age population during this time, given that the only institution of the city could not cover all the existing demand. The methodological procedures used include the consultation and analysis of several local newspapers, minutes of City Council, official reports of the acting mayor and of the school inspector, among other corresponding documents for the period mentioned. From these sources, and using the theoretical references aimed to analyze educational institutions, it was sought to understand the local, state and national political relations that interfered in educational issues. In the second part of this paper it was possible to know the routine of the institution, using as main source the minutes of pedagogical meetings held between 1944 and 1962, the period that corresponds to Esmeralda Rocha Bunazar s management, principal that headed Grupo Escolar Minas Gerais for eighteen consecutive years. Besides highlighting the subjects involved in the educational process (principal, teachers, students, parents and school inspectors), special attention was given to teaching, disciplinary and religious practices, for being recurring themes in teachers meetings. It was found therefore that such practices were dialectically related, since religious issues were incorporated to pedagogical practices which were in turn influenced by discipline practices and so on. In conclusion, it was found that Minas Gerais School Group had its installation delayed due to political agreements, because the building of the school was assigned to the Battalion of the Armed Forces of Minas Gerais. Only in the 1940 s the institution opened its doors to the community to start playing its educational role.